2004
DOI: 10.1055/s-2004-834915
|View full text |Cite
|
Sign up to set email alerts
|

A Total Synthesis of 1-Methoxycanthin-6-one: An Efficient One-Pot Synthesis of the Canthin-6-one Skeleton from β-Carboline-1-carbaldehyde

Abstract: A total synthesis of naturally occurring 1-methoxycanthin-6-one is described. In this synthesis, we achieved one-pot conversion from b-carboline-1-carbaldehyde to the canthin-6-one skeleton by the sequential addition of lithium ketene acetal in LiHMDS solution followed by the addition of EtOH in the reaction mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…NMR spectra were obtained on a Bruker Avance 250 spectrometer operating at 250 and 62.9 MHz for 1 H and 13 C NMR spectra, respectively (CAI de Resonancia MagnØtica Nuclear, Universidad Complutense; Madrid, Spain) with the signal of the residual nondeuterated solvent as an internal stan- and water (1 mL). The resulting solid was washed with refluxing MeOH for 1 h to complete its purification, leading to compounds 1 a-c, 1 g, 1 h and 1 j-p. All aldehydes used in this work were commercially available, with the exception of b-carboline-1-carbaldehyde [49] and b-carboline-3-carbaldehyde, [50] which were prepared according to literature methods. Compounds 1 a, [51] 1b-c, [52] 1 df, [41] 1 e, [53] 1 l-m, [54] and 1 n [55] were known in the literature, although their analytical characterization was normally incomplete.…”
Section: Experimental Section Chemistrymentioning
confidence: 99%
“…NMR spectra were obtained on a Bruker Avance 250 spectrometer operating at 250 and 62.9 MHz for 1 H and 13 C NMR spectra, respectively (CAI de Resonancia MagnØtica Nuclear, Universidad Complutense; Madrid, Spain) with the signal of the residual nondeuterated solvent as an internal stan- and water (1 mL). The resulting solid was washed with refluxing MeOH for 1 h to complete its purification, leading to compounds 1 a-c, 1 g, 1 h and 1 j-p. All aldehydes used in this work were commercially available, with the exception of b-carboline-1-carbaldehyde [49] and b-carboline-3-carbaldehyde, [50] which were prepared according to literature methods. Compounds 1 a, [51] 1b-c, [52] 1 df, [41] 1 e, [53] 1 l-m, [54] and 1 n [55] were known in the literature, although their analytical characterization was normally incomplete.…”
Section: Experimental Section Chemistrymentioning
confidence: 99%
“…The resulting solid was washed with refluxing MeOH for 1 h to complete its purification, leading to compounds 1 a – c , 1 g, 1 h and 1 j – p . All aldehydes used in this work were commercially available, with the exception of β‐carboline‐1‐carbaldehyde49 and β‐carboline‐3‐carbaldehyde,50 which were prepared according to literature methods. Compounds 1 a, 51 1b – c, 52 1 d – f ,41 1 e, 53 1 l – m, 54 and 1 n 55 were known in the literature, although their analytical characterization was normally incomplete.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting 5-azidocanthin-6-one was further transformed to 5-aminocanthin-6-one via catalytic reduction (Figure 6). Suzuki et al [39] reported the synthesis of canthin-6-one derivative from 1-formyl-9H-β-carboline and its 4-methoxy derivative. In addition many researchers are continuous trying to do more research in this field.…”
Section: Synthesis Of β-Carbolinementioning
confidence: 99%